The effect of e-service quality on customer satisfaction with repurchase intention as a moderating variable in the Soco by Sociolla application - Utami, Tyas Widia; Hidayat, Agus Maolana (Edelweiss Applied Science and Technology, 2024)
This study investigates the influence of e-service quality on customer satisfaction with repurchase intention as a moderating variable, focusing on the SOCO by Sociolla app. Using a quantitative approach and a sample of 400 respondents, this research applies Partial Least Squares (PLS) analysis to assess the relationships among e-service quality, customer satisfaction, and repurchase intention. The results reveal that e-service quality significantly impacts customer satisfaction, indicating that higher service quality fosters customer contentment in digital shopping experiences. Additionally, repurchase intention slightly moderates this relationship, suggesting that consumers' likelihood to repurchase may influence their satisfaction levels derived from service quality. These findings highlight the need for e-commerce platforms, particularly in the beauty industry, to optimize e-service quality to boost satisfaction and repurchase rates. This research contributes to understanding digital consumer behavior and offers practical insights for enhancing service quality in online retail.